Down-regulation of AMPK/PPARδ signalling promotes endoplasmic reticulum stress-induced endothelial dysfunction in adult rat offspring exposed to maternal diabetes. Issue 10 (20th August 2021) - Luo, Hao; Lan, Cong; Fan, Chao; Gong, Xue; Chen, Caiyu; Yu, Cheng; Wang, Jialiang; Luo, Xiaoli; Hu, Cuimei; Jose, Pedro A; Xu, Zaicheng; Zeng, Chunyu
Abstract: Aims: Exposure to maternal diabetes is associated with increased prevalence of hypertension in the offspring. The mechanisms underlying the prenatal programming of hypertension remain unclear. Because endoplasmic reticulum (ER) stress plays a key role in vascular endothelial dysfunction in hypertension, we investigated whether aberrant ER stress causes endothelial dysfunction and high blood pressure in the offspring of dams with diabetes. Methods and results: Pregnant Sprague-Dawley rats were intraperitoneally injected with streptozotocin (35 mg/kg) or citrate buffer at Day 0 of gestation. Compared with control mother offspring (CMO), the diabetic mother offspring (DMO) had higher blood pressure and impaired endothelium-dependent relaxation in mesenteric arteries, accompanied by decreased AMPK phosphorylation and PPARδ expression, increased ER stress markers, and reactive oxygen species (ROS) levels. The inhibition of ER stress reversed these aberrant changes in DMO. Ex vivo treatment of mesenteric arteries with an AMPK agonist (A769662) or a PPARδ agonist (GW1516) improved the impaired EDR in DMO and reversed the tunicamycin-induced ER stress, ROS production, and EDR impairment in mesenteric arteries from CMO. The effects of A769662 were abolished by co-treatment with GSK0660 (PPARδ antagonist), whereas the effects of GW1516 were unaffected by Compound C (AMPK inhibitor). Conclusion: These results suggest an abnormal foetal programming of vascular endothelial function in offspring of rats with maternal diabetes that is associated with increased ER stress, which can be ascribed to down-regulation of AMPK/PPARδ signalling cascade. Graphical Abstract: